2009
DOI: 10.5194/acp-9-1711-2009
|View full text |Cite
|
Sign up to set email alerts
|

Summertime PM<sub>2.5</sub> ionic species in four major cities of China: nitrate formation in an ammonia-deficient atmosphere

Abstract: Abstract. Strong atmospheric photochemistry in summer can produce a significant amount of secondary aerosols, which may have a large impact on regional air quality and visibility. In the study reported herein, we analyzed sulfate, nitrate, and ammonium in PM 2.5 samples collected using a 24-h filter system at suburban and rural sites near four major cities in China (Beijing, Shanghai, Guangzhou, and Lanzhou). Overall, the PM 2.5 mass concentrations were high (with a mean value of 55-68 g µgm −3 ), which reflec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
371
10
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(419 citation statements)
references
References 65 publications
31
371
10
7
Order By: Relevance
“…In addition; nighttime secondary NO 3 − formation involves the hydrolysis of dinitrogen-pentaoxide (N 2 O 5 ) through the heterogeneous reaction on aerosol surfaces and higher relative humidity enhances the heterogeneous hydrolysis of N 2 O 5 (Ravishankara et al, 1997;Jacob, 2000;Pathak et al, 2009). Brown et al (2004) have suggested that the conversion efficiency of NO x to HNO 3 during nighttime can be equivalent to the daytime photochemical conversion.…”
Section: Sulphur and Nitrogen Oxidation Ratios (Sor And Nor)mentioning
confidence: 99%
“…In addition; nighttime secondary NO 3 − formation involves the hydrolysis of dinitrogen-pentaoxide (N 2 O 5 ) through the heterogeneous reaction on aerosol surfaces and higher relative humidity enhances the heterogeneous hydrolysis of N 2 O 5 (Ravishankara et al, 1997;Jacob, 2000;Pathak et al, 2009). Brown et al (2004) have suggested that the conversion efficiency of NO x to HNO 3 during nighttime can be equivalent to the daytime photochemical conversion.…”
Section: Sulphur and Nitrogen Oxidation Ratios (Sor And Nor)mentioning
confidence: 99%
“…The F SA values for the ambient aerosols are diverse, reaching to more than 0.60 under ammonium-poor condition and to less than 0.40 under ammonium-rich condition (Pathak et al 2009). In this study, the C-RUV calibration curve obtained from ammonium-poor aerosols was extrapolated to ammonium-rich aerosol such as NH 4 HSO 4 aerosol (F SA = 0.50) and (NH 4 ) 3 H(SO 4 ) 2 aerosol (F SA = 0.40) under various RHs.…”
Section: Extrapolation Of C-ruv To Weakly Acidic Aerosolmentioning
confidence: 99%
“…When the ammonia gas is not sufficient to completely neutralize sulfuric acid aerosol, the atmospheric aerosol tends to be acidic. The pH of ambient aerosols collected in US and some of the European and Asian countries ranges from −1 to 3, indicating that atmospheric aerosol is quite acidic (Pathak et al 2009). It has been known that both dry and wet deposition of acidic aerosol cause damage to building materials and endanger ecological integrity (Likens et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…While the formation mechanisms of nitrate are relatively well known, the relative contributions of different mechanisms can have large variability and uncertainties. Pathak et al (2009) found that the heterogeneous hydrolysis of N 2 O 5 contributed 50 %-100 % of the nighttime enhancement of nitrate concentration in Beijing. WRF-Chem model simulations showed only 21 % enhancement of nitrate during highly polluted days (Su et al, 2016).…”
Section: Introductionmentioning
confidence: 99%